PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN JENGKOL (Pithecellobium lobatum Benth) TERHADAP KADAR GLUKOSA DARAH PADA TIKUS PUTIH JANTAN (Rattus novergicus) - Firmansyah, Gunawan; Wijaya, Hasty Martha; Palupi, Dian Arsanti; Karima, Nur Aini; Riyanto, Bagus (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2025)
Diabetes mellitus is a type of chronic disease with specific characteristics with blood glucose levels above normal. Jengkol leaves are one part of the plant that contains flavonoids, saponins and tannins that can be used as a treatment for DM. This study aims to understand the impact of administering ethanol extract of jengkol leaves (Phitecellobium lobatum Benth) on blood glucose levels in male white rats (Rattus novergicus). This study is an experimental study applying a pretest and posttest control group design. After checking glucose levels on H0, the rats were induced using alloxan monohydrate intraperitoneally. The rats were separated into 5 groups including the positive control group given metformin, the negative control group given Na-CMC, control groups 1, 2, 3 were given ethanol extract of jengkol leaves with a continuous dose of 500, 1000, 1500 mg, given orally for 14 days. The checks were carried out on H7 and H14 after being given alloxan induction. The results of the study were analyzed using the Shapiro Wilk normality test and data homogeneity test. Then continued One Way ANOVA analysis and Tukey Post Hoc test on H7 and H14 treatments. The results showed no significant difference in the positive control with the 1000 mg and 1500 mg dose groups, this indicates that both doses of jengkol leaf ethanol extract have a balanced ability with the positive control group. Ethanol extract of jengkol leaves has an effect on reducing blood glucose levels in male Wistar strain rats and the effective dose of jengkol leaf ethanol extract on blood glucose levels in male white Wistar strain rats given alloxan monohydrate is 1000 mg/KgBW.